Effect analysis on the application of IFRS 10 compared with the IAS 27 - Morgado, Maria Salomé de Jesus Martins (2014)
This study investigates the changes caused on the application of IFRS 10 Consolidated Financial Statements compared with the previous guidance IAS 27 Consolidated and Separated Financial Statements on the Consolidated Financial Statements. IFRS 10 replaces the IAS 27 and is effective application started, for the annuals periods beginning on or after 1 January 2013. With the objective of understanding it’s possible effects, this work started to compare the standard currently applied (IAS 27) with the IFRS 10, and it is identified a number of differences, some of them that could be only complements or effective instructions of implicit references already on IAS 27 and with no practice consequences, but there are also existent differences. To demonstrate the identified differences, some illustrative examples are used in this study, some of them adapted from the IFRS 10. An exhaustive search was also done, through the universe of European Firms, with the intention of finding entities already applying the IFRS 10, to be able to analyze the impact of IFRS 10 on the scope of consolidation. Although in this early stage it was not so easy to find a case study, BASF Group and is participation on an investee, is presented in this study as a real example of a change in the consolidation method caused by the revised definition of control. The result of this work gives support to real differences on the scope of consolidation with the application of IFRS 10. Some investors will control investees that they did not consolidate under IAS 27, and other investors will not consolidate investees that were consolidated under IAS 27. And also significant judgment will be needed on the applying of the new definition of control, and also the application guidance of the IFRS 10.